Propylthiouracil-induced mitochondrial dysfunction in liver and its relevance to drug-induced hepatotoxicity - Akram Jamshidzadeh 1,2, Hossein Niknahad, Reza Heidari, Maryam Azadbakht, Forouzan Khodaei, Mohammad Reza Arabnezhad, Omid Farshad (Tabriz University of Medical Sciences, 2017)
Background: Propylthiouracil (PTU) administration is associated with several cases of hepatotoxicity, especially in children. The mechanism(s) of PTU-induced hepatotoxicity is obscure. In the current study, we aimed to assess the effect of PTU on hepatocytes mitochondria in different experimental models. Methods: Mice were treated with PTU (10, 20, 40, 80, and 100 mg/kg, i.p) then, the liver mitochondria were isolated and evaluated. Moreover, liver mitochondria were isolated from normal mice and incubated with increasing concentrations of PTU (10 µM-1 mM). Mitochondrial dehydrogenases activity, mitochondrial membrane potential, mitochondrial swelling, and mitochondrial adenosine triphosphate (ATP) content were monitored. Results: PTU hepatotoxicity was biochemically evident in mice by increased serum biomarkers of liver injury. PTU also caused a decrease in mitochondrial dehydrogenases activity, increased mitochondrial swelling, depleted mitochondrial ATP, and caused mitochondrial depolarization both in vitro and in vivo. Conclusion: Our data suggest mitochondrial dysfunction as a mechanism for PTU-induced hepatotoxicity